Acute Toxicity of Bajakah Tampala (Spatholobus littoralis Hassk) Ethanolic Extract on The Microanatomy of Rat Spleens - Arini Miftahul Jannah; Diah Wulandari Rousdy; Elvi Rusmiyanto Pancaning Wardoyo (Jurnal Biodjati, 2025)
The utilization of bajakah tampala (Spatholobus littoralis Hassk) as a herbal medicine has been passed down through generations within the community in Kalimantan. However, no comprehensive studies have investigated the effects of consuming this herbal medicine without a standardized safe dose. This study aimed to determine the spleen microanatomy after administration of an acute dose of S. littoralis stem ethanolic extract. The stems of S. littoralis utilized in this study were obtained from the Sungai Ambawang Forest in Kubu Raya, West Kalimantan. These stems underwent maceration with 96% ethanol solvent. This study used a completely random design with four treatments, which included distilled water and S. littoralis stem ethanolic extract at three doses: 300; 2000; and 5000 mg/kg BW. Each treatment had five replicates. The results showed that the administration of extract doses above 2000 mg/kg BW caused a significant decrease in the diameter of the splenic white pulp, and the spleen’s microanatomy revealed that the boundary between the periarteriolar lymphoid sheaths (PALS) and the lymphoid follicles disappeared, as well as lymphoid follicles that shrank in size. This shows that the administration of extract doses above 2000 mg/kg BW causes symptoms of damage to the spleen microanatomy of experimental animals.